Disruption of gut homeostasis by opioids accelerates HIV disease progression - Meng, Jingjing; Sindberg, Gregory M.; Roy, Sabita (Frontiers in Microbiology, 2015)
Cumulative studies during the past 30 years have established the correlation between opioid abuse and human immunodeficiency virus (HIV) infection. Further studies also demonstrate that opioid addiction is associated with faster progression to AIDS in patients. Recently, it was revealed that disruption of gut homeostasis and subsequent microbial translocation play important roles in pathological activation of the immune system during HIV infection and contributes to accelerated disease progression. Similarly, opioids have been shown to modulate gut immunity and induce gut bacterial translocation. This review will explore the mechanisms by which opioids accelerate HIV disease progression by disrupting gut homeostasis. Better understanding of these mechanisms will facilitate the search for new therapeutic interventions to treat HIV infection especially in opioid abusing population.